Proclaimed and Real Purposes of Policies for Regulation of Access to Higher Education in Brazil (1997-2017) (Global Journal of Human-Social Science, 2024)
The article aimed to analyze the purposes of educational policies that reformed the last stage of basic education (high school) and higher education in Brazil, between 1997 and 2017, considering the mode of state regulation established in its relationship with access to education Brazilian public superior. Starting from a Marxian theoretical perspective, we undertook descriptive and explanatory research taking as sources the legal provisions enacted in the period that reformed secondary education and higher education in the period established in the study. The analysis of the proclaimed and real purposes of the devices showed that although there are specific regulations for higher education, access to this level is also impacted by policies relating to basic education, especially secondary education, which is why we infer that the regulation of basic and higher education produced in the period calibrates processes of state regulation of access to higher education.
Keywords: reforms; high school; university education; regulation of access to higher education